1980
DOI: 10.1111/j.1365-2621.1980.tb04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Growth Regulators on Plant Nutrients

Abstract: Tomato, pea, and New Zealand spinach plants were treated with gibberellic acid, Cycocel, and Phosfon. The tomatoes, green peas, and spinach leaves were analyzed for proteins, soluble carbohydrates, starch, ascorbic acid, niacin, β‐carotene, and titratable acidity. Cycocel and Phosfon increased proteins in all products, starch in green peas and tomatoes, and ascorbic acid in spinach and tomatoes. Cycocel increased β‐carotene in spinach and tomatoes. Phosfon increased β‐carotene in tomatoes and soluble carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…Maximum TSS (⁰Brix) was found in T5 (4.95) and minimum TSS was found in T0 (3.80). Similar results were found by Gelmesa et al (2012) and Graham and Ballesteros (2006) in tomato.…”
Section: Total Soluble Solidsupporting
confidence: 92%
“…Maximum TSS (⁰Brix) was found in T5 (4.95) and minimum TSS was found in T0 (3.80). Similar results were found by Gelmesa et al (2012) and Graham and Ballesteros (2006) in tomato.…”
Section: Total Soluble Solidsupporting
confidence: 92%
“…This was due to the synthesis of nonprotein nitrogen componnents while in NemaSnap, greater synthesis of protein (amino acids) occurred. Graham and Ballesteros (1980) found a 43% increase of protein (% nitrogen X 6.25) in Phaseolus vulgaris cultivar Bountiful treated with Phosfon D. However, this reported protein value may also contain protein plus nonprotein nitrogen as we found in Eagle (Fig. 1).…”
Section: Methodscontrasting
confidence: 72%
“…Phosfon D applied as a foliar spray and as a soil drench to cowpea seedlings decreased the plant height, increased root length, and increased the yield (Jain and Yadava, 1981). Graham and Ballesteros (1980) demonstrated that soil-applied Phosfon D increased soluble carbohydrate, starch, and protein in green peas (snap beans).…”
Section: Introductionmentioning
confidence: 99%
“…These growth regulators provide the grower with some control of harvest maturity of crops and thus influence nutritional quality of harvested products. Preharvest application of gibberellins increased protein and ascorbic acid contents of spinach, green peas and tomatoes (Graham and Ballesteros 1980) and ascorbic acid of sweet cherries (Drake et al 1978).…”
Section: Preharvest Conditionsmentioning
confidence: 99%